2018
DOI: 10.7120/09627286.27.3.275
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the welfare level of intensive fattening pig farms in Germany with the Welfare Quality® protocol: does farm size matter?

Abstract: The housing condition of pig (Sus scrofa) fattening farms are increasingly receiving criticism, because they are associated with impaired animal welfare. Consumers view the increase in farm sizes critically, even though scientifically based knowledge on the relationship between farm size and welfare is still limited. Therefore, the aim of this study was to assess the welfare level of conventional fattening pig farms in Germany and to evaluate the relationship between farm size and animal welfare level. In tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…According to the WQ ® protocol, growers and fatteners in Slovenian conventional farms were rated as acceptable, while Slovenian alternative farms were rated as enhanced. In Germany, the welfare of fattening pigs on conventional farms was assessed and, regardless of farm size, the overall WQ classifications 'excellent' and 'not classified' were not recorded in any of the farms, while 'enhanced' and 'acceptable' were achieved by 80 and 20 % of the farms, respectively (Meyer-Hamme et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…According to the WQ ® protocol, growers and fatteners in Slovenian conventional farms were rated as acceptable, while Slovenian alternative farms were rated as enhanced. In Germany, the welfare of fattening pigs on conventional farms was assessed and, regardless of farm size, the overall WQ classifications 'excellent' and 'not classified' were not recorded in any of the farms, while 'enhanced' and 'acceptable' were achieved by 80 and 20 % of the farms, respectively (Meyer-Hamme et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that water supply has also emerged as an important animal welfare issue in other protocols and species (e.g. Meyer-Hamme et al 2018 ; Otten et al 2020 )…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that water supply has also emerged as an important animal welfare issue in other protocols and species (e.g. Meyer-Hamme et al 2018;Otten et al 2020) The measure 'Cooling system' was identified as an area of concern for weaner-to-finisher pigs. To comply with current Danish legislation, a means of cooling must be available for all pigs above 20 kg (Ministry of Food, Agriculture and Fisheries 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In conventional farming systems, multiple factors, including environmental factors [ 20 , 31 ], lead to soiled bodies. e.g., seasonal effects, cleanliness of the pen and the type of flooring [ 14 ]. Temple et al [ 20 ] also found that moderately soiled body measurements appeared to be sensitive to differences between intensive farming systems.…”
Section: Discussionmentioning
confidence: 99%
“…There are many studies on the correlation between the results of animal-based parameters and environment-based parameters. In particular, the most important environmental determinants of pig welfare were space allowance and bedding material [ 14 ]. However, improving farm animal welfare mainly based on these two variables is difficult to achieve because most pig farms in intensive livestock production system use concrete or metal slatted floors that does not allow bedding materials to be used.…”
Section: Introductionmentioning
confidence: 99%